Ecological Niche Modeling to Calculate Ideal Sites to Introduce a Natural Enemy: The Case of Apanteles opuntiarum (Hymenoptera: Braconidae) to Control Cactoblastis cactorum (Lepidoptera: Pyralidae) in North America - Nidia Bélgica Pérez-De la O; Saúl Espinosa-Zaragoza; Víctor López-Martínez; Stephen D. Hight; Laura Varone (Insects, 2020)
The cactus moth, Cactoblastis cactorum (Berg) (Lepidoptera: Pyralidae), is an invasive species in North America where it threatens Opuntia native populations. The insect is expanding its distribution along the United States Gulf Coast. In the search for alternative strategies to reduce its impact, the introduction of a natural enemy, Apanteles opuntiarum Martínez and Berta (Hymenoptera: Braconidae), is being pursued as a biological control option. To identify promising areas to intentionally introduce A. opuntiarum for the control of C. cactorum, we estimated the overlap of fundamental ecological niches of the two species to predict their common geographic distributions using the BAM diagram. Models were based on native distributional data for both species, 19 bioclimatic variables, and the Maxent algorithm to calculate the environmental suitability of both species in North America. The environmental suitability of C. cactorum in North America was projected from Florida to Texas (United States) along the Gulf coastal areas, reaching Mexico in northern regions. Apanteles opuntiarum environmental suitability showed a substantial similarity with the calculations for C. cactorum in the United States. Intentional introductions of A. opuntiarum in the actual distribution areas of the cactus moth are predicted to be successful; A. opuntiarum will find its host in an environment conducive to its survival and dispersal.